Characteristics of Graves' disease in children and adolescents in Nanjing: A retrospective investigation study - Xie, Hang; Chen, Dandan; Zhang, Ju; Yang, Ruize; Gu, Wei; Wang, Xu (Frontiers in Public Health, 2022)
Objective This cross-sectional study analyzed the clinical characteristics of newly diagnosed Graves' disease (GD) in children and adolescents to provide clinical evidence for the early diagnosis of GD. Method From 2013 to 2019, information on children and adolescents with newly diagnosed GD admitted to the Department of Endocrinology, Children's Hospital of Nanjing Medical University, was collected, including clinical features and laboratory tests. The data were summarized and statistically analyzed. Result This study included 204 cases of newly diagnosed GD, with 158 females and 46 males. The average age at initial diagnosis was 8.9 ± 2.9 years. A total of 132 cases (64.7%) had symptoms before puberty, and 72 cases (35.3%) had symptoms during puberty. Goiter was detected in 193 cases (94.6%). There were 140 cases (68.6%) of exophthalmos, and 21.4% (30/140) were infiltrative. At initial diagnosis, 10 cases (4.9%) reported leukopenia, 18 cases (8.8%) reported neutropenia, and 15 cases (7.4%) reported mild anemia. There was 1 (0.5%) case of thrombocytopenia and 1 (0.5%) case of agranulocytosis. Fifty-four cases (26.5%) had impaired liver function. Conclusion GD is more common in female children and adolescents. Parents may ignore their children's hypermetabolic symptoms in the early stages of GD. Routine blood and liver function tests are recommended at initial diagnosis to exclude abnormal hemogram and liver function.